A Comparative Study on Some Functional and Antioxidant Properties of Kilka Meat, Fishmeal, and Stickwater Protein Hydrolysates. Issue 7 (9th August 2018) - Mahdabi, Mahdad; Hosseini Shekarabi, Seyed Pezhman
ABSTRACT: This study determined some antioxidative activities and functional properties of hydrolyzed proteins prepared from kilka ( Clupeonella sp .) meat (KMH), kilka fishmeal (KFH), and stickwater (SWH). The highest degree of hydrolysis (DH) was 25.02% ( p  < 0.05) in SWH; however, the difference in DH between KMH and KFH was not significant. KFH had the highest protein content (85.69%) compared with other hydrolysis samples. The Fourier transform infrared spectra of KFH had the highest amide absorption picks ( p  < 0.05). Solubility at neutral pH was 84.09%, 86.00%, and 93.08% for KMH, KFH, and SWH, respectively. The highest fat absorption capacity was obtained with KFH (204 mg/50 mg). KFH also showed the best foaming properties with 25.66% foaming capacity and proper stability during 60 min ( p  < 0.05). The highest and lowest whiteness values were obtained in KMH (72.33%) and SWH (36.54%), respectively ( p  < 0.05). The highest 2, 2-diphenyl-1-picrylhydrazyl (DPPH) (IC50 value of 1.99 mg/mL) and 2, 2ʹ-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) (IC50 value of 2.00 mg/mL) radical scavenging activities were measured at the highest concentrations (40 mg/mL) in KFH ( p  < 0.05). KFH had the best functional and antioxidant properties, while SWH had a strong ability to inhibit lipid oxidation. Therefore, stickwater from fishmeal production factories is a potential resource for use in developing value-added products instead of being discarded.